Korean Wave dalam Fanatisme dan Konstruksi Gaya Hidup Generasi Z - Karina Amaliantami Putri; Amirudin Amirudin; Mulyo Hadi Purnomo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
The purpose of this research is to understand and analyze the lifestyles of the Generation Z which is formed because of their status as a Korean Wave fanatic fan. This study uses ethnographic research methods consisting of participation observation and depth interviews with five Generation Z of women who are fanatic fan of the Korean Wave. Based on the results of this study, there are four main components which are the factors why the Generation Z becomes fanatically attached with the Korean Wave, (1) high level of admiration and likes, (2) addiction, (3) feeling of wanting, and (4) loyalty. This paper then saw that the element of fanaticism inherent in Generation Z, which lead to indirect creation of a flow of the process of forming their lifestyle identity, which are the selection of Korean Wave as entertainment, spending a lot of time doing activities related to the Korean Wave, and use the money for the Korean Wave.